IMPLEMENTASI PELAYANAN PERNIKAHAN DI MASA PPKM DARURAT PERSPEKTIF MASLAHAH MURSALAH (STUDI DI KUA KECAMATAN JUNREJO KOTA BATU) - Achmad Syarifuddin; Ahmad Subekti; Humaidi Humaidi (Jurnal Hikmatina, 2022)
The Implementation period of Community Activity Restrictions (PPKM) has a major impact on all community activities in Indonesia. Likewise with community service activities organized by government agencies. The Office of Religious Affairs (KUA) as the spearhead of community service is required to provide optimal services in the midst of the Covid-19 outbreak in accordance with the instructions of the Director General of Islamic Community Guidance Number P-001/ DJ. III/Hk.007/07/2021. In this study, researchers conducted research at KUA Junrejo Subdistrict of Batu City using qualitative research methods of case study type. Data collection techniques use interviews, documentation, and observation. The results of this observation for people's lives according to maslahah mursalah who answer the problems of society. Antigen swab test policy for both brides-to-be, marriage guardians and 2 (two) witnesses as an additional condition in marriage in the Emergency PPKM Period. The antigen swab test is useful to reduce the number of Covid-19 spread in Indonesia. Keyword: PPKM Period, Marriage